2012
DOI: 10.1118/1.3681948
|View full text |Cite
|
Sign up to set email alerts
|

Verification of proton range, position, and intensity in IMPT with a 3D liquid scintillator detector system

Abstract: Purpose: Intensity-modulated proton therapy (IMPT) using spot scanned proton beams relies on the delivery of a large number of beamlets to shape the dose distribution in a highly conformal manner. The authors have developed a 3D system based on liquid scintillator to measure the spatial location, intensity, and depth of penetration (energy) of the proton beamlets in near real-time. Methods: The detector system consists of a 20 Â 20 Â 20 cc liquid scintillator (LS) material in a light tight enclosure connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 18 publications
0
59
0
2
Order By: Relevance
“…Several features of large scintillators enable them to be good candidates for dosimetric measurements of proton beam such as fast response and high spatial resolution 7. Recently, large 3D‐volume liquid scintillator detectors were used to verify proton range and position for scanned proton beams and showed that they were able to provide precise position results within 0.7% and an accuracy in proton range to within 0.3 mm on average 8, 9. However, the materials making up a liquid scintillator are not suitable for hospital environments due to toxicity and the need to deoxygenate the scintillator prior to use to optimize the light output 10.…”
Section: Introductionmentioning
confidence: 99%
“…Several features of large scintillators enable them to be good candidates for dosimetric measurements of proton beam such as fast response and high spatial resolution 7. Recently, large 3D‐volume liquid scintillator detectors were used to verify proton range and position for scanned proton beams and showed that they were able to provide precise position results within 0.7% and an accuracy in proton range to within 0.3 mm on average 8, 9. However, the materials making up a liquid scintillator are not suitable for hospital environments due to toxicity and the need to deoxygenate the scintillator prior to use to optimize the light output 10.…”
Section: Introductionmentioning
confidence: 99%
“…Although proton scanning beam characteristics, such as beam spot size, location, and duration, should be confirmed during the QA process, real-time data are difficult to acquire using a conventional dosimetric system [11][12][13], suggesting the applicability of the proposed AFCRS system. Recent studies showed that scintillator detector system viewed by a CCD camera is capable to measure the spatial location, intensity, and depth of penetration (energy) of the proton beams in realtime [14,15]. Although scintillator detector is a good candidate for the real-time proton dosimeter, there are some limitations.…”
Section: Discussionmentioning
confidence: 98%
“…First, they are tissue- or water-equivalent, enabling dose detection with minimal field perturbation (Ingram et al 2015). Second, they have high spatial resolution (Archambault et al 2012). Third, they exhibit good temporal resolution, with nanosecond scintillation-response time and detection time in the range of milliseconds.…”
Section: Introductionmentioning
confidence: 99%